An approach to realistic evaluation of antihypertensive regimes. Issue 615 (January 1977) - Carlisle, R.; Akinkugbe, O. O.; Basile, U.; Solagbade, M. E.
Abstract : Where practicable, all subjects found with onset-phase-four blood pressure of 90 mmHg or more after referral were allocated, on a random basis, to alternative antihypertensive regimes at a dosage related to response. Of those 110 receiving either guanethidine, methyldopa or debrisoquine, only the group on methyldopa had significantly reduced median blood pressure by two out of four criteria and after 6 months of therapy. It is nevertheless considered that by assessment of the total group more significant conclusions can be drawn for an eventual attempt to control hypertension on a community basis than by studies of highly selected groups treated under unusually favourable conditions.